The Relationship Between Environmental Sanitation And The Incidence Of Diarrhea In Toddlers In The Work Area Of The Kalidawir District Community Health Center, Tulungagung Regency - Aksol Muntaha, Muhammad Ibnu; Setyo Budi Susanto (Universitas STRADA Indonesia, 2024)
Sanitation is one of the most important challenges for developing countries because according to WHO one of the causes of diarrhea is lack of access to sanitation which is still too low. Environmental Sanitation is the health status of an environment which includes housing, sewage disposal, provision of clean water and so on. The aim of the research determines the relationship between environmental sanitation factors and complaints of diarrhea among toddlers in Kalidawir sub-district, Tulungagung district. In this research, researchers used descriptive analytical methods with a cross sectional approach. With a sample of 92 toddlers with respondents namely mothers of toddlers in the Kalidawir health center working area, Tulungagung district. The results of research on the incidence of diarrhea in toddlers found that the majority of toddlers experienced diarrhea, namely 80 respondents (87%). Sources of clean water and the incidence of diarrhea in toddlers. There is an influence between sources of clean water and the incidence of diarrhea in toddlers. It is known that the majority of respondents who have a clean water source meet the requirements with the incidence of diarrhea being 53 respondents (57.6%). The latrine facility with the most respondents having a latrine that meets the requirements has an incidence of diarrhea of 50 respondents (54.3) while respondents with a latrine that does not meet the requirements has an incidence of diarrhea of 30 respondents (32.6%). Waste processing and the incidence of diarrhea in toddlers with the most respondents having waste and waste processing did not meet the requirements with the incidence of diarrhea as many as 71 respondents (77.2%). Meanwhile, 9 respondents (9.8%) had waste processing that met the requirements. There is a need to increase outreach on environmental sanitation programs, including clean water management, healthy latrine facilities and waste processing so that people are aware and increase clean and healthy behavior among the community.